A comparative assessment of the EU's reforms to merger control and antitrust enforcement. (2nd September 2015) - Levy, Nicholas; Frisch, Sven; Waksman, Alexander
Abstract : In the early 2000s, EU merger control and EU antitrust enforcement each underwent significant change. In many ways, both sets of reforms achieved their objectives. The Commission's application of the Merger Regulation following the reforms implemented in the wake of the Airtours, Schneider, and Tetra Laval judgments is widely considered to have been a success. Commission practice has become developed to a point where counsel are generally able to predict with reasonable certainty the analytical framework that will be applied in any given case, the economic and other evidence that will likely be considered probative, the duration of the Commission's review, and the probable outcome. By contrast, the Commission's application of Articles 101 and 102 has in certain respects become less predictable as new issues and challenges have arisen. The challenge for the Commission in the coming years will be to bring to the application of EU antitrust rules the same rigor, consistency, and predictability that today characterizes EU merger control.